Surprises in probability : seventeen short stories - Tijms, Henk (CRC Press, Taylor & Francis Group, 2019)
"This book bundles together a variety of probability applications through entertaining stories that will appeal to a broad readership. What are the best stopping rules for the dating problem, the Chow-Robbins game and the devil's penny game? How the gambler's fallacy created the Venice-53 hysteria in the national Italian lottery. These questions and many others are addressed in seventeen short chapters that can be read independently. The engaging stories are instructive as well and demonstrate valuable probabilistic ideas"--